"So that his mind will open": Parental perceptions of early childhood education in urbanizing Ghana. (November 2017) - Kabay, Sarah; Wolf, Sharon; Yoshikawa, Hirokazu
Highlights: Parents prioritize behavior and socialization in children's preschool experience. Parents are critical of play in preschool because they view it as unstructured time. Urbanization affects parents expectations for children's early learning/development. ECE should address urban African realities such as linguistic and migrant diversity. Abstract: As policy makers and practitioners work to increase access to early childhood education (ECE) and to improve the quality of existing services, it is important that the field consider the perspective of a key stakeholder: parents. This study analyzes 33 interviews with parents of young children in urban Ghana. The interviews investigate (1) what parents believe to be the purpose of ECE, and (2) parents' perspective on what and how young children should learn. Results are analyzed around five themes: play, homework, mobility, language and diversity, and age of entry into school. Implications for global ECE policy are discussed.